Cooperation Between Memory Systems: Acetylcholine Release in the Amygdala Correlates Positively With Performance on a Hippocampus-Dependent Task. - McIntyre, Christa K.; Marriott, Lisa K.; Gold, Paul E. (Behavioral Neuroscience, 2003)
The present experiment examined the relationship between release of acetylcholine (ACh) in the amygdala and performance on a hippocampus-dependent spatial working memory task. Using in vivo microdialysis, the authors measured ACh release in rats during testing on a spontaneous alternation task. Amygdala ACh release was positively correlated with performance on the hippocampus-dependent task. These findings suggest that activation of the amygdala promotes processing in other neural systems important for learning and memory. Reprinted by permission of the publisher.